2016
DOI: 10.1134/s0012496616010038
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic tumor cell death under the influence of the cytotoxic complex Tag7–Hsp70 is induced by interaction with the TNFR1 receptor

Abstract: The results of comparative analysis of interaction between the protein cytotoxic complex Tag 7-Hsp70 and the Tag 7 component of this complex with TNFR1 receptor in solution and in tumor cells are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Another mechanism, how extracellular HSP70 might affect tumour cells is the complex formation of the innate immunity protein Tag7 with HSP70 [62,63]. It has been shown that interaction of the Tag7-HSP70 complex with TNFR1 triggers the activation of RIP1-kinase, an increase in intracellular concentration of Ca 2þ ions and an activation of calpains which result in the permeabilization of lysosomal membranes [63][64][65][66].…”
Section: Role Of Intracellular Membrane and Extracellular Heat Shock Protein 70 In Tumour Cellsmentioning
confidence: 99%
“…Another mechanism, how extracellular HSP70 might affect tumour cells is the complex formation of the innate immunity protein Tag7 with HSP70 [62,63]. It has been shown that interaction of the Tag7-HSP70 complex with TNFR1 triggers the activation of RIP1-kinase, an increase in intracellular concentration of Ca 2þ ions and an activation of calpains which result in the permeabilization of lysosomal membranes [63][64][65][66].…”
Section: Role Of Intracellular Membrane and Extracellular Heat Shock Protein 70 In Tumour Cellsmentioning
confidence: 99%